VO2Max in Soccer Players: Comparison of Interval Training and Continuous Running - Bahtra, Ridho; Crisari, Silvio; Dinata, Windo Wiria; Susanto, Nugroho; Andria, Yogi (Faculty of Sport and Health Sciences, 2023)
Soccer is a complex sport that requires excellent physical condition. One of the important physical conditions that soccer players have is endurance or VO2Max. Therefore, a training method is needed to increase the VO2Max of soccer players, to maintain the skills they have. This study aims to compare interval training and continuous running in increasing the VO2Max of soccer players. This study is quasi-experimental with a two-group post-test design. The subjects in this study were 24 people with an average age of 23.46 years. All players are members of one of the amateur clubs in West Sumatra. They are players who only train 3 times a week. The subjects were then grouped into 2 groups through the ordinary matched pairing technique so that the interval training group was 12 people and the continuous running group was 12 people. The player's VO2Max data is obtained by conducting a test using a multi-stage fitness test (bleep test). After all the data is obtained then analyzed using the t-test. The results indicate a significant difference between the two training methods, where interval training is more effective than continuous running, it can be seen that tcount > ttable = 2.17 > 1.796. So, it can be concluded that interval training is better than continuous running in improving the VO2Max of soccer players.